Chronic myeloid leukemia with complex karyotypes: Prognosis and therapeutic approaches. Issue 5 (14th November 2018) - Asnafi, Ali Amin; Deris Zayeri, Zeinab; Shahrabi, Saeid; Zibara, Kazem; Vosughi, Tina
Abstract: Objective and Background: Chronic myeloid leukemia (CML) is a neoplastic disease whose genetic and cytogenetic changes play important roles in prognosis and treatment strategies. Philadelphia (Ph) translocation t(9;22)(q34;q11) is a diagnostic and prognostic biomarker in CML. Methods: Pubmed and Google Scholar databases were searched for English language articles from 1975 to 2017 containing the terms CML; Additional chromosomal abnormalities; Philadelphia translocation; Prognosis; and Treatment. Discussion: Approximately 10–12% of CML patients exhibit additional chromosomal aberrations (ACAs) in chronic phase and blast crisis. ACAs emergence may cause different features in CML patients according to Ph pattern. For instance, deletion of chromosome 9 derivation is associated to patient's bad survival, whereas monosomy 7 develops myeloid dysplastic syndrome (MDS) or acute myeloid leukemia (AML) in CML patients with Ph‐negative pattern. And ACAs in Ph‐positive CML is considered as a failure in the management of CML with imatinib. Conclusion: CML classification using different features such as Ph and ACAs can play a decisive role in the evaluation of treatment responses in patients, for example, CML patients with Ph negative and monosomy 7 develop MDS or CML patient –Y and extra copy of Ph have a good response to tyrosine kinase inhibitors, therefore, classifications according to Ph and ACAs play an important role in choosing better treatment protocols and therapeutic strategies. Karyotype analysis in CML patients with complex karyotype shows unrandom pattern so ACAs can be great clue in medical guidelines. Abstract : Additional chromosomal aberrations may cause different features on chronic myeloid leukemia (CML) patients according to Philadelphia translocation pattern. Karyotype analysis in CML patients with complex karyotype shows unrandom pattern. Incidence of additional chromosome and variant translocation is higher in blast crisis of CML.